CO-CREATING CUSTOMER VALUE IN THE PLATFORM ECONOMY: INTEGRATING ENTREPRENEURIAL STRATEGY AND MARKETING INNOVATION - Margono, Hery (Ikatan Dosen Menulis, 2025)
The development of the platform-based economy has transformed the way companies and customers interact, moving from a one-way relationship to a more open and interconnected process. Customer engagement is no longer limited to the consumption stage but extends to various points of interaction that shape the overall experience. This situation requires companies to adapt their approaches to maintain relevance amidst increasingly complex customer behavior. This study aims to examine how the integration of entrepreneurial strategy and marketing innovation can drive customer engagement and create sustainable value in the platform economy. This study uses a qualitative approach, utilizing various relevant literature sources as a basis for analysis. The results indicate that customer engagement is formed through consistent interactions and accumulated experiences across various touchpoints. Adaptive entrepreneurial strategies and relevant marketing innovations play a role in strengthening customer participation and building more meaningful relationships. The integration of strategic direction and marketing implementation impacts the quality of the resulting interactions, thereby supporting business sustainability and strengthening the company's competitive position.